Nonseismic Signals in the Ocean: Indicators of Deep Sea and Seafloor Processes on Ocean‐Bottom Seismometer Data. (5th August 2019) - Batsi, Evangelia; Tsang‐Hin‐Sun, Eve; Klingelhoefer, Frauke; Bayrakci, Gaye; Chang, Emmy T.Y.; Lin, Jing‐Yi; Dellong, David; Monteil, Clément; Géli, Louis
Abstract: Ocean‐bottom seismometers (OBSs) commonly record short‐duration events (SDEs) that could be described by all of these characteristics: (i) duration <1 s, (ii) one single‐wave train with no identified P nor S wave arrivals, and (iii) a dominant frequency usually between 4 and 30 Hz. In many areas, SDEs have been associated with gas‐ or fluid‐related processes near cold seeps or hydrothermal vents, although fish bumps, instrumental, or current‐generated noise have been proposed as possible sources. In order to address some remaining issues, this study presents results from in situ and laboratory experiments combined with observations from two contrasting areas, the Sea of Marmara (Turkey) and the Chilean subduction zone. The in situ experiment was conducted at the European Multidisciplinary Seafloor and water column Observatory‐Molène submarine observatory (near Brest, France) and consisted in continuously monitoring two OBSs with a camera. The images revealed that no fish regularly bumped into the instruments. Laboratory experiments aimed at reproducing SDEs' waveforms by injecting air or water in a tank filled by sand and seawater and monitored with an OBS. Injecting air in the sediments produced waveforms very similar to the observed SDEs, while injecting air in the water column did not, constraining the source of SDEs in the seafloor sediments. Finally, the systematic analysis of two real data sets revealed that it is possible to discriminate gas‐related SDEs from biological or sea state‐related noise from simple source parameters, such as the temporal mode of occurrence, the back azimuth, and the dominant frequency. Plain Language Summary: Ocean‐bottom seismometers are instruments deployed on the ocean floor to study earthquakes and other sources of noise. They can record large teleseismic earthquakes, like all seismometers, and more specifically smaller submarine earthquakes. However, they also record noise generated by volcanoes, anthropogenic, or biological activity (whale calls). In particular, short events, lasting less than a second, have been reported worldwide with similar characteristics but their origin is still debated. They have been interpreted as fish hitting the instrument, signals generated by hydrothermal activity or by gas expelled out of the sediments. Here, we continuously monitored ocean‐bottom seismometers with a camera and show that no fish accidentally stroke the instruments. Then, during laboratory experiments we demonstrate that gas expelled out of the marine sediments into the water can produce short signals very similar to those recorded by the seismometers in real conditions. Finally, we analyzed data from two experiments, one in the Sea of Marmara and the other offshore Chile. We show that short events are generated by gas expelled into the water. This study thus demonstrates the use of marine seismometers to monitor processes related to gas in the sea, which has direct impacts for better quantifying natural risks. Key Points: Short‐duration high‐amplitude events routinely recorded on marine seismometers are not created by fish bumping into the geophone In laboratory experiments, the waveforms of these events are well reproduced by fluid migration in the sediments We propose three simple source parameters to discriminate gas‐related short‐duration events in OBS data